2006
DOI: 10.1038/ja.2006.63
|View full text |Cite
|
Sign up to set email alerts
|

Four New Macrocyclic Trichothecenes from Two Strains of Marine-derived Fungi of the Genus Myrothecium

Abstract: Three new macrocyclic trichothecenes, named 12Ј-hydroxyroridin E (1), roridin Q (2), and 2Ј,3Ј-deoxyroritoxin D (3), were isolated from the marinederived fungus Myrothecium roridum TUF 98F42, and a new macrocyclic trichothecene, named roridin R (4), was isolated from Myrothecium sp. TUF 02F6 together with roridins A and H and isororidin E. The structures of new compounds were determined on the basis of their spectral data. Compound 2 possessed a unique ether moiety at the 13Ј position of 1. Compound 4 was a 2Ј… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 11 publications
2
23
0
Order By: Relevance
“…Although 91 displayed IC 50 values of 25 and 15 ng mL −1 towards HL-60 and L1210 cell lines, respectively, its activity was reduced about 80 fold in comparison to 86 [65]. In a subsequent study, the same fungal strain was reported to produce three new macrocyclic trichothecenes, 12′-hydroxyroridin E ( 87 ), roridin Q ( 88 ), and 2′,3′-deoxyroritoxin D ( 98 ), while one new compound, roridin R (2′,3′-dihydro-2′-hydroxyroridin H, 97 ), was isolated from Myrothecium sp., together with the known foridins A and H, and isororidin E [66]. 88 is characterized by a unique ether moiety at C-13′ and thus contains a third hydroxyacid moiety.…”
Section: Examples Of Terpenoidsmentioning
confidence: 99%
“…Although 91 displayed IC 50 values of 25 and 15 ng mL −1 towards HL-60 and L1210 cell lines, respectively, its activity was reduced about 80 fold in comparison to 86 [65]. In a subsequent study, the same fungal strain was reported to produce three new macrocyclic trichothecenes, 12′-hydroxyroridin E ( 87 ), roridin Q ( 88 ), and 2′,3′-deoxyroritoxin D ( 98 ), while one new compound, roridin R (2′,3′-dihydro-2′-hydroxyroridin H, 97 ), was isolated from Myrothecium sp., together with the known foridins A and H, and isororidin E [66]. 88 is characterized by a unique ether moiety at C-13′ and thus contains a third hydroxyacid moiety.…”
Section: Examples Of Terpenoidsmentioning
confidence: 99%
“…Another two new antibacterial agents were isolated from a marine Aspergillus sp. strain 05F16, active against S. aureus and Escherichia coli [34]. Three new alkaloids were obtained from the ethyl acetate extract of a marinederived fungal strain, Aspergillus sydowi PFW1-13 which display significant antimicrobial activities against E. coli, Bacillus subtilis, and Micrococcus lysoleikticus [35].…”
Section: Introductionmentioning
confidence: 99%
“…For general backgroud, see: Amagata et al (2003); Namikoshi et al (2001); Alvi et al (2002); Xu et al (2006); Abbas et al (2002); Kaneko et al (1982); Allen et al (1987); Jarvis & Midiwo (1982); Cremer & Pople (1975). For related literature, see: Shen et al (2006).…”
Section: Related Literaturementioning
confidence: 99%